An Impairment of Salivary Gland Function in Rheumatoid Arthritis: Association with Change in Salivary Biomarkers and Disease Activity - Wasan L Abdulla; Batool H A-Ghurabi; Khalid H Gathwan (College of Dentistry/ University of Baghdad, 2016)
Background: Rheumatoid arthritis is a chronic inflammatory autoimmune disease characterized by joint inflammation, involvement of exocrine salivary and lacrimal glands may occur as extra-articular maniÂ¬festations in this disease. This study aimed to provide evidence of altered in function and composition of salivary gland in patients with rheumatoid arthritis by determine salivary flow rate and some biochemical parameters(total protein, amylase, peroxidase) and to investigate the relationship between disease activity and changes in function and composition of salivary gland. Materials and Methods: Fifty five patients with RA (7 males and 48 females) were enrolled in this study with age range (20-69) years. The patients were separated into two groups in proportion to their salivation: normal salivation group (37) and hypo salivation group (18). Thirty five (9 male and 26 female) apparently healthy volunteers were also participated in the study. Three ml of unstimulated saliva was collected from all patients and control to determine salivary flow rate on one hand and salivary total protein, Î±-amylase and peroxidase by colorimetric method on other hand. Results:Resultsshowed that there is highly significant decrease (P< 0.01; p< 0.001) in the median salivary levels of (flow rate, total protein, Î±-amylase and peroxidase) among RA patients when compared to control. There was highly significant reduction (P< 0.01) in median salivary levels of flow rate, total protein, Î±-amylase and peroxidase in two study groups (normal salivation and hypo salivation) as compared to that in control group. Also the levels of all these parameters (sialometry and sialochemistry) were significantly decrease (P =0.00) in RA patients with hypo salivation as compared to that in patients with normal salivation. There was strong positive correlation between total protein and salivary flow rate (r= 0.651, P=0.000), in one hand, and on the other hand, there was strong positive correlation between Î±-amylase and both salivary flow rate (r=623, P= 0.000) and total protein r=658, P=0.000). Conclusion: These findings indicate that the changes in salivary composition may represent involvement of salivary glands in patients with rheumatoid arthritis.